The influence of somatostatin analogues on the incidence of pancreatic fistulas and postoperative morbidity in patients undergoing pancreatic resection: A Bayesian network meta-analysis - Zonghao Hou; Shengxiang Hou; Zhixin Wang; Haijiu Wang; Manjun Deng; Haining Fan (PLoS ONE, 2025)
Background Pancreatic resection is a critical treatment for pancreatic cancer and other pancreatic diseases. Somatostatin analogs are commonly used to prevent complications following pancreatic resection, but their efficacy and safety remain debated. Methods Following PRISMA guidelines, a systematic search was conducted across multiple databases, including PubMed, EMBASE, Scopus, Cochrane Library, Ovid, ClinicalTrials.gov, Web of Science, CNKI, and WanFang Data. The search focused on studies comparing the use of somatostatin analogs after pancreatic surgery. Key outcomes included postoperative pancreatic fistula (POPF), clinically relevant POPF (CR-POPF), mortality, and morbidity. Statistical analysis was performed using a consistency model, calculating relative risk ratios (RR) with 95% confidence intervals (CI), and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) tool was used to assess the quality of evidence. Results In the absence of stratification based on the surgical procedure, For POPF prevention, pasireotide showed a relative risk (RR) of 0.46 (95% CI: 0.23, 0.87, Low) compared to placebo, and octreotide had an RR of 0.76 (95% CI: 0.66, 0.88, Moderate). Somatostatin and vapreotide showed no significant differences. In preventing CR-POPF, pasireotide had an RR of 0.46 (95% CI: 0.23, 0.86, Low), somatostatin had an RR of 0.60 (95% CI: 0.36, 0.99, Moderate), and octreotide had an RR of 0.61 (95% CI: 0.39, 0.94, Moderate). Regarding postoperative mortality, vapreotide showed an RR of 0 (95% CI: 0.00, 0.29, Low), while octreotide, somatostatin and pasireotide did not demonstrate significant effects. For reducing morbidity, octreotide had an RR of 0.74 (95% CI: 0.66, 0.82, Moderate), somatostatin had an RR of 0.76 (95% CI: 0.66, 0.87, Moderate), vapreotide and pasireotide showed no significant effect.In Pancreaticoduodenectomy subgroup, somatostatin showed an RR of 0.22(95% CI: 0.03, 0.84, Moderate) for preventing CR-POPF.For all the other outcomes, neither somatostatin nor octreotide proved effective. Conclusion While robust evidence confirms the efficacy of octreotide in preventing POPF, a critical concern regarding its inconsistent efficacy within the PD subgroup persists. This variability indicates that the overall clinical benefit of octreotide may be predominantly attributable to its utility in non-PD pancreatic resections.